Effect of dual glucose-dependent insulinotropic peptide/glucagon-like peptide-1 receptor agonist on weight loss in subjects with obesity - Zaffina, Isabella; Pelle, Maria Chiara; Armentaro, Giuseppe; Giofrè, Federica; Cassano, Velia; Sciacqua, Angela; Arturi, Franco (Frontiers in Endocrinology, 2023)
The occurrence of obesity is an increasing issue worldwide, especially in industrialized countries. Weight loss is important both to treat obesity and to prevent development of complications. To date, several drugs are used to treat obesity, but their efficacy is modest. Thus, new anti-obesity treatments are needed. Recently, there has been an increased interest to develop incretins that combine body weight-lowering and glucose-lowering effects. Therefore, a new drug that simultaneously coactivates both the glucose-dependent insulinotropic polypeptide (GIP) receptor (GIPR) and the glucagon-like peptide-1 receptor (GLP-1R) has been developed. Tirzepatide, the first of this class, improves glycemic control by increasing insulin sensitivity and lipid metabolism as well as by reducing body weight. Combining the activation of the two receptors, a stronger improvement of β cell function offers a more effective treatment of diabetes and obesity with fewer adverse effects than selective GLP-1R agonists. In the present review, we discuss progress in the use of GIPR and GLP-1R coagonists and review literature from in vitro studies, animal studies, and human trials, highlighting the synergistic mechanisms of tirzepatide.